Size Effect and Insolvency Profiles among the SMEs: An Empirical Investigation - Lai, Fong Woon (2014)
Purpose: This purpose of this study is to examine the effect of size on insolvency of small medium enterprises (SMEs) in Malaysia. The conceptual framework is designed using the recommended measures, variables, concepts and models. Design/ methodology/ approach: A total sample of 229 businesses which consisted of small (57), medium (111) and large (61) SMEs. The data were obtained from the Registrar of Companies (ROC). Percentile method (25, 50, 75) was adopted to categorize the size of SMEs using their total assets values. Testing of signification of size effect incorporated the Z-scores Altman’s Model and the nonparametric statistical techniques (Kruskal-Wallis Test and Mann-Whitney U test) for empirical testing based on the cross-sectional data. Findings: The results indicate that size effect was significant only on profitability measures. There were no significant differences among the small, medium and large SMEs with regard to insolvency scores. In general, about 55 per cent of the large SMEs fell under the bankruptcy category, as compared to 39 per cent of the small SMEs and about 47 per cent of the medium SMEs. Large SMEs faced greater financial risk and thus, faced greater risk for insolvency. Research Implications: Most of the large firms tend to register a higher score on insolvency as compared to that of small and medium firms. Admittedly, large firms, though look more stable financially, however, they seem to be the first to ‘collapse’ (financially distressed) as supported by the Altman’s Z-scores. On the contrary, despite the liquidity problem faced by the small firms in the short run, they do not show any symptoms to default. Meanwhile, the medium firms manage to sustain at average performance with regard to insolvency. This signifies that comparatively, large SMEs are bound to face greater financial risk as compared to small and medium SMEs. Practical Implications: Low gearing ratios registered by the large firms may be offering misleading information as the ratios could denote large amounts of borrowing (thus, higher financing costs) without the support of sufficient profit margin. Small SMEs are generally constrained by the shortterm liquidity as result of relatively lower profit margin, however, they are well prepared to adjust themselves to the business environment even with higher gearing. Originality/value: There is no much work capturing the size effect among the SMEs particularly in Malaysia. Generally, studies suggest that smaller firms use more of debt financing (especially current debt), rely more on internal funds and loans from stockholders to finance their operations, do not use much external equity relative to larger firms and thus they differ on returns and smaller firms seem to face higher cost of equity capital. Consistent with these arguments, firm size does have impact on financial risk and cause insolvency. Lack of equity and long-term debt could be the main detrimental factors to insolvency and future growth and becomes a major cause of failure. In this regard, SMEs are always treated as small firms and hence, the general characteristics of small firms are applied on SMEs. Literature on SMEs’ financial sustainability is limited to the characteristics of small firms where most of them are listed firms. These findings may not be applicable for SMEs. Hence, there is a need to relook at the size of SMEs at micro level as the size effect among the SMEs remainssignificant and continues to be a magnifier for long term sustainability. Hence, it is worth to explore the impact of firm size on insolvency profile of SMEs.